FORMING LOGICAL THINKING IN ELEMENTARY STUDENTS THROUGH THE USE OF CHESS IN COURSE AND EXTRA-COURSE ACTIVITIES (Eureka Journal of Education & Learning Technologies, 2026)
This article discusses the theoretical and pedagogical foundations and practical possibilities of forming logical thinking in primary school students through the use of chess in classroom and extracurricular activities. The study scientifically analyzes the role of chess in developing students' analytical thinking, decision-making in problem situations, understanding cause-and-effect relationships, and independent thinking skills. It also shows effective forms and methods of integrating chess classes into the educational process, mechanisms for the gradual development of logical thinking through didactic games and exercises. The results of the study confirm that chess is an effective pedagogical tool for ensuring the intellectual development of primary school students, and methodological recommendations for practicing teachers are developed.
Keywords: chess game, primary school students, logical thinking, curricular and extracurricular activities, intellectual development, analytical thinking, didactic games, pedagogical technologies, independent thinking, effectiveness of the educational process.